Psychopharmacological Treatment, Intraocular Pressure and the Risk of Glaucoma: A Review of Literature - Adela Magdalena Ciobanu (Journal of Clinical Medicine, 2021)
Through the years, the available psychopharmacological treatments have expanded with numerous new drugs. Besides weight gain, gastro-intestinal problems or Parkinson-like symptoms, ocular adverse effects of psychiatric drugs have been reported. These adverse effects are not common, but can be dangerous for the patient. This review summarises the current knowledge on the risk of raised intraocular pressure and glaucoma entailed by psychopharmacological treatment. Also, it provides updated data for clinicians involved in the treatment of patients with glaucoma or glaucoma risk factors. For this purpose, we performed an extensive literature search in the PubMed database using specific terms. Selective serotonin and noradrenaline reuptake inhibitors are the best evidenced as having no association with glaucoma. Antipsychotics, and especially first generation, seem to have no correlation with an increased intraocular pressure and therefore possibly with a risk of glaucoma, although a special attention should be paid when using ziprasidone. Tricyclic antidepressants, benzodiazepines and topiramate should be avoided in patients diagnosed with glaucoma or at risk. Clinicians should be aware of the possible psychotropic drug induced glaucoma and monitor at risk patients closely in order to prevent this condition. Irrespective of the psychopharmacological regimen taken into consideration, the glaucoma patient should be under the strict supervision of the ophthalmologist.